The Book of Acts in the Setting of Hellenistic History - Hemer, Colin J (Mohr Siebeck, 1989)
The Book of Acts in the Setting of Hellenistic History
PublicationDate: 20191210
Keywords: Hellenistic History -- Neues Testament -- Kirchengeschichte -- Array